2004
DOI: 10.24200/jams.vol9iss1pp21-25
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Content of Commercial Inorganic Fertilizers Used in the Kingdom of Saudi Arabia

Abstract: In recent years much concern has been given to toxic heavy metals, which enter the human food chain. Application of inorganic fertilizers is considered one of the potential routes of such entry, in this work 74 samples of commercial fertilizers marketed in the Kingdom of Saudi Arabia were analyzed for their heavy metal concentrations. Fertilizer samples included 20 samples of phosphatic fertilizers [monoammonium phosphate (MAP), diammonium phosphate (DAP) and triple superphosphate (TSP)], 11 samples of liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 0 publications
1
53
1
1
Order By: Relevance
“…The pH value and the percentage of clay content determine the solubility of metals in the soil and their availability for uptake by plants (Golia et al 2008). Heavy metals content usually decreases from clay to coarse silt due to relatively high surface area of clay minerals and weak pH dependence of CEC (Modaihsh et al 2004). From our study, it is evident that there is an obvious relationship between clay content and the amount of heavy metals in soils.…”
Section: Profile Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH value and the percentage of clay content determine the solubility of metals in the soil and their availability for uptake by plants (Golia et al 2008). Heavy metals content usually decreases from clay to coarse silt due to relatively high surface area of clay minerals and weak pH dependence of CEC (Modaihsh et al 2004). From our study, it is evident that there is an obvious relationship between clay content and the amount of heavy metals in soils.…”
Section: Profile Distributionmentioning
confidence: 99%
“…Heavy metals can also accumulate in the soil due to application of liquid and solid manure (or their derivatives, compost or sludge) or inorganic fertilizers (Huang and Jin 2008). A previous study on heavy metal contents in phosphatic fertilizers (DAP) revealed the following order: Co (11.8) \ Cd (33.2) \ Ni (72.1) \ Cr (249.3) mg kg -1 (Modaihsh et al 2004). In general, DAP (diammonium phosphate) fertilizers contain 10 mg kg -1 Cd; 71 mg kg…”
Section: Effects Of Fertilizer Usagementioning
confidence: 99%
“…The presence of heavy metals in surface water is caused by weathering of soils, rocks and by anthropogenic activities that disturb the natural distribution of heavy metals in surface water [1]. Soils may become contaminated by the accumulation of heavy metals through emissions from the rapidly expanding industrial areas, mine tailings, disposal of high metal wastes, leaded gasoline and paints, land application of fertilizers, animal manures, sewage sludge, pesticides, wastewater irrigation, coal combustion residues, spillage of petrochemicals, and atmospheric deposition [2,3]. Long term use of sewage effluent for irrigation contaminates the soil and vegetables to such extent that it becomes toxic to plants and causes the deterioration of the soil that contains considerable amount of potentially harmful substances of heavy metals like Cr, Fe, Cu, Pb, Zn and Cd [3].…”
Section: Introductionmentioning
confidence: 99%
“…The most significant natural sources are weathering of minerals, erosion and volcanic activity, while the anthropogenic sources depend upon human activities such as mining, smelting, electroplating, use of pesticides and phosphate fertilizer discharge, as well biosolids (e.g., livestock manures, composts, and municipal sewage sludge), atmospheric deposition, etc. [14,[43][44][45][46]47]. The disturbance of nature's slowly occurring geochemical cycle of metals by man results in accumulation of one or more of heavy metals in the soil and waters, and above defined levels, this is enough to cause risk to human health, plants, animals and aquatic biota [48].…”
Section: Sources Of Heavy Metal In the Environmentmentioning
confidence: 99%